Development and Community Empowerment in Local Wisdom Based Ecotourism in Sambangan Village, Sukasada District, Buleleng Regency, Bali Province - Toto Noerasto; Anak Agung Ayu Dewi Larantika; I Made Mardika; I Gusti Agung Istri Anindyagani (Cita konsultindo, 2025)
This study aimed to analyze the development and empowerment of the community in managing ecotourism based on local wisdom in Sambangan Village, Sukasada District, Buleleng Regency, Bali. Initial observations indicated that the village's tourism potential, including ten waterfalls, cultural attractions, and man-made tourism facilities, had not been optimally managed due to limited development strategies and human resource capacity. This study employed a qualitative method, collecting data through in-depth interviews, observations, and document analysis. The results showed that ecotourism development based on local wisdom successfully utilized natural, cultural, and artificial tourism potentials to attract visitors and improve community welfare. Local wisdom, reflected in the spirit of mutual cooperation, agricultural traditions, arts, and culture, strengthened tourism governance, with community members actively participating in village deliberations, training, homestay management, digital marketing, and preservation of traditional arts and handicrafts. Institutions such as LPHD and POKDARWIS served as coordination platforms to maintain environmental sustainability and ensure responsible tourism. The study produced a model of community empowerment that supported local economic improvement while preserving cultural values and environmental sustainability. The findings emphasized the importance of community collaboration and the utilization of local wisdom as a strategy for inclusive, sustainable, and adaptive ecotourism development.